Dishonesty in everyday life and its policy implications - Nina Mazar; Dan Ariely (Federal Reserve Bank of Boston, 2006)
Dishonest acts are all too prevalent in day-to-day life. In the current review, we examine some possible psychological causes for such dishonesty that go beyond the standard economic considerations of probability and value of external payoffs. We propose a general model of dishonest behavior that includes also internal psychological reward mechanisms for honesty and dishonesty, and we point to the implications of this model in terms of curbing dishonesty.
Keywords: 330; performance-based incentives